2023
DOI: 10.1186/s12871-023-01973-w
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of postoperative IL-6 and IL-10 levels following Erector Spinae Plane Block (ESPB) and classical Thoracolumbar Interfascial Plane (TLIP) block in a posterior lumbar decompression and stabilization procedure: a randomized controlled trial

Abstract: Background and objectives The erector spinae plane block (ESPB) and classical thoracolumbar interfascial plane (TLIP) block can reduce postoperative pain in lumbar surgery. In this study, we compared the efficacy of ESPB and classical TLIP block in providing perioperative analgesia in patients undergoing lumbar posterior decompression and stabilization by comparing postoperative pain, opioid consumption, and IL-6 and IL-10 serum concentrations between ESPB and classical TLIP block. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 36 publications
(42 reference statements)
0
15
0
Order By: Relevance
“…A total of 914 studies were identified by the search strategy, and after all duplicates were deleted, 488 articles entered the screening process, and 391 articles were excluded through title and abstract. After reading the full text, 5 studies [28][29][30][31][32] met the inclusion criteria and were included in the quantitative analysis, as shown in Figure 1. All studies were recent and published between 2020 and 2023, comprising outcomes of ESPB versus TLIP block in patients undergoing spine surgery.…”
Section: Study Search and Selectionmentioning
confidence: 99%
See 4 more Smart Citations
“…A total of 914 studies were identified by the search strategy, and after all duplicates were deleted, 488 articles entered the screening process, and 391 articles were excluded through title and abstract. After reading the full text, 5 studies [28][29][30][31][32] met the inclusion criteria and were included in the quantitative analysis, as shown in Figure 1. All studies were recent and published between 2020 and 2023, comprising outcomes of ESPB versus TLIP block in patients undergoing spine surgery.…”
Section: Study Search and Selectionmentioning
confidence: 99%
“…The 5 studies included 4 RCTs 28,29,31,32 from India, Indonesia, China, and Turkey in English and 1 cohort study 30 in Chinese. In all, 457 patients were included, and there were 234 (51.2%) patients in ESPB group and 223 (48.8%) patients in TLIP block group.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 3 more Smart Citations